Design and fabrication of automatic cat feeder / Muhammad Hisyamuddin Muhammad Razif - Muhammad Razif, Muhammad Hisyamuddin (2024)
This Automatic Cat Feeder was created to make taking care of pets easier. The primary issue was that owners were not home to give their pets enough food, and the cat food would always get stuck in the space between the tank and the container. Pet owners can use a smartphone app to customize feeding food with the Automatic Cat Feeder. Food getting stuck in automatic cat feeders is still an issue, despite the variety of designs available. Food will not become trapped between the tank and the container with this automatic cat feeder. We're using an automatic system in this project, which the user can operate from a distance with a phone. This project's primary component is the ESP8266, which is related to other components such as Transmission Control Protocol/Internet Protocol (TCP/IP) network software and a WiFi microchip. The cat feeder and phone are typically connected via an ESP8266. The food will drop when the owner simply presses the "FOOD" button on the phone. Thus, flexible control is possible with the Automatic Cat Feeder.